Dampak Pendapatan Asli Daerah, Transfer Ke Daerah Terhadap Kemandirian Fiskal Provinsi Maluku: Case Study Provinsi Maluku - Liline, Ledy Jeane; Khaeril (Insan Cita Bongaya Research Journal, 2024)
The Maluku Province, like many other regions in Indonesia, still heavily relies on transfers from the central government to finance its expenditures. This dependency can limit fiscal autonomy and the region's flexibility in managing its budget according to local needs.This study aims to examine the impact of Regional Original Revenue (PAD), Transferred to the regions (TKD) on the Fiscal Independence of Maluku Province. Research Methods Applied quantitative research. With a literature review and description of the financial statements of the Maluku Provincial Budget Realization during the year period (2018-2022), and analyzed with several formulas on Fiscal Independence and Regional Independence Index.The results of the study show that: (1) The degree of fiscal decentralization of the Maluku Provincial Government during 2018-2022, is still